Pengaruh Metode Permodelan dan Pengetahuan Apresiasi Sastra terhadap Kemampuan Membaca Puisi - Hamdan Hamdan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The purpose of the study was to know the influence of modeling method and literary appreciation knowledge toward reciting poetry ability of seventh graders students' of SMPN Remban in academic year 2016/2017. The data was the result of literary appreciaton knowledge test and reciting poetry ability. VII.3 class used modeling method while VII.2 class used literary appreciation knowledge. This was experimental study toward students' ability in reciting poetry. Annova two ways analysis was used in analyzing the data. The findings showed that (a) there was influence between modeling method with reciting poetry ability, where Fvalue > Ftable or 2.482 > 0,3132, (b) literary appreciation knowledge influence toward reciting poetry ability Fvalue 24,716 > Ftable 0,3132, and (c)there was interaction between modeling method and literary aporeciation knowledge toward reciting poetry ability Fvalue 30,037 > F table 0,3132. In summary, students who taught by modeling method were better than students' who taught by literary appreciation in reciting poetry. Keywords: Modeling method, literary appreciation, reciting poetry ability